SII@EDU social innovation initiatives: English language empowerment camp / Wan Nurul Elia Haslee Sharil, Munirah Mohd Izam and Fazyudi Ahmad Nadzri - Haslee Sharil, Wan Nurul Elia; Mohd Izam, Munirah; Ahmad Nadzri, Fazyudi (Universiti Teknologi MARA in collaboration with Faculty of Education (EDU), Universiti Teknologi MARA, Shah Alam, Selangor, 2020)
The one-day camp was organised by the Bukit Jelutong Residents'Association (BJRA) for the benefit of both Sekolah Kebangsaan and Sekolah Menengah Kebangsaan Bukit Jelutong, Shah Alam. Its primary objective was to increase the school students' proficiency in English.